(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the prevalence of anxiety, depression, and stress among high school students in Xuan Dong and Cam My communes, Dong Nai province, in 2025. Methods: A cross-sectional descriptive study was conducted in 2025 among 400 high school students in Xuan Dong and Cam My communes to describe the prevalence of anxiety, depression, and stress. Results: Results showed that 65.5% of students experienced anxiety, 50.3% experienced stress, and 32.8% experienced depression. The prevalence of mild, moderate, and severe stress was 26.5%, 18.3% and 5.5%, respectively. For anxiety, the prevalence of mild, moderate, and severe levels was 24.7%, 39.3% and 1.5%, respectively. For depression, the prevalence of mild and moderate levels was 29.0% and 3.8%, respectively. Male students had a lower risk of stress and anxiety compared to female students (0.66 times and 0.78 times, respectively). The risks of stress, anxiety, and depression increased by grade level and were highest among 12th-grade students (stress 3.25 times, anxiety 1.83 times, and depression 4.68 times) compared with 10th-grade students. Engaging in physical activity at least 4 times per week was associated with a reduced risk of depression. Conclusion: These findings indicate that anxiety, depression, and stress are common among high school students and may negatively affect academic performance and psychosocial development. Therefore, it is necessary to establish psychological support programs for students, particularly female students and those in their final year of high school.